Dimensions of Sufism Within The Islamic Religious Education Curriculum in Higher Education - Muhammad, Farhad; Abitolkha, Amir Maliki; Dodi, Limas (Nazhruna: Jurnal Pendidikan Islam, 2024)
Education is currently increasingly directing students toward a passion for competition. Competitive model education can blunt emotional and spiritual intelligence to inhibit the growth of vibrant and affective traits in student personalities. Therefore, the Dimensions of Sufism in education can function as an alternative to stem the disruption and problems of millennial education. This study uses a multi-case study type of Higher Education in East Java, Indonesia. The dimensions of Sufism in Islamic religious education in higher education show their uniqueness. The unique fact is the teaching of Sufism at Darul Ulum University (UNDAR) Jombang, which prioritizes the teaching of the Trisula course with three pillars: the concept of boarding schools, Sufi order, and campus. Sufism values are taught in all study programs and are internalized practically through the ritual of the Sufi order in the structured campus activity program. At the same time, the uniqueness of Sufism teaching in the other six higher educations emphasizes the basis of the cluster in the field of science. This study argues that the injection of Sufism values into the structure of the higher education curriculum is a primary need to equip intellect intelligence to control themselves against the dynamics of life.